Probiotics Bacillus licheniformis Improves Intestinal Health of Subclinical Necrotic Enteritis-Challenged Broilers - Kan, Liugang; Guo, Fangshen; Liu, Yan; Pham, Van Hieu; Guo, Yuming; Wang, Zhong (Frontiers in Microbiology, 2021)
Necrotic enteritis infection poses a serious threat to poultry production, and there is an urgent need for effective antibiotic alternatives to control it with the global ban on in-feed antibiotics. This study was conducted to investigate the effects of dietary Bacillus licheniformis replacing enramycin on the growth performance and, intestinal health of subclinical necrotic enteritis (SNE) challenged broilers. 504 1-day-old Arbor Acres male chickens were selected and subsequently assigned into 3 treatment, including PC (basal diet + SNE challenge), PA (basal diet extra 10 mg/kg enramycin + SNE challenge), PG (basal diet extra 3.20 × 109 and 1.60 × 109 CFU Bacillus licheniformis per kg diet during 1~21 days and 22~42 days respectively + SNE challenge). Results showed that Bacillus licheniformis significantly decreased the intestinal lesion scores and down-regulated the claudin-3 mRNA levels in jejunum of SNE-infected broilers on day 25, but increased the Mucin-2 gene expression in broilers on day 42. In addition, Bacillus licheniformis significantly up-regulated the mRNA levels of TRIF and NF-κB of SNE challenged broilers compared with the control group on day 25 and TLR-4, TRIF compared with the PC control and the antibiotic group on day 42. The mRNA expression of HSP60, HSP90 and GLP-2 were up-regulated in Bacillus licheniformis supplementary group on day 25 and 42 compared with group PC. LEfSe analysis showed that the relative abundance of Lachnospiraceae_UCG_010 were enriched in the PG group compared with group PC and Clostridiales_vadinBB60, Rnminococcaceae_NK4A214 were enriched compared with group PA. PICRUSt analysis found that the metabolism of cofactors and vitamins, amino acid metabolism and carbohydrate metabolism pathways were enriched while energy metabolism, membrane transport, cell motility and lipid metabolism were suppressed in B. licheniformis supplemented-groups as compare with the PC control. In conclusion, dietary supplementation of Bacillus licheniformis alleviated the intestinal damage caused by SNE challenge coincided with modulating intestinal microflora structure and barrier function as well as regulating intestinal mucosal immune responses.